3D geometries of normal faults in a brittle-ductile sedimentary cover: Analogue modelling. (July 2018) - Vasquez, Lina; Nalpas, Thierry; Ballard, Jean-François; Le Carlier De Veslud, Christian; Simon, Brendan; Dauteuil, Olivier; Bernard, Xavier Du
Abstract: It is well known that ductile layers play a major role in the style and location of deformation. However, at the scale of a single normal fault, the impact of rheological layering is poorly constrained and badly understood, and there is a lack of information regarding the influence of several décollement levels within a sedimentary cover on the single fault geometry under purely extensive deformation. We present small-scale experiments that were built with interbedded layers of brittle and ductile materials and with minimum initial constraints (only a velocity discontinuity at the base of the experiment) on the normal fault geometry in order to investigate the influence of controlled parameters such as extension velocity, rate of extension, ductile thickness and varying stratigraphy on the 3D fault geometry. These experiments showed a broad-spectrum of tectonic features such as grabens, ramp-flat-ramp normal faults and reverse faults. Forced folds are associated with fault flats that develop in the décollement levels (refraction of the fault angle). One of the key points is that the normal fault geometry displays large variations in both direction and dip, despite the imposed homogeneous extension. This result is exclusively related to the presence of décollement levels, and is not associated with any global/regional variation in extension direction and/or inversion. Highlights: Normal faults geometries with décollement levels. Geneses of flats, forced fold and reverse faults along normal faults.